THE EFFECT OF FUROSEMIDE IN CRITICALLY ILL ADULT PATIENTS – A NARRATIVE REVIEW - Putri, Cyndi Yulanda; Nugroho, Agung Endro; Widyati, Widyati (Majalah Farmaseutik, 2024)
Background: Fluid overload is the common condition in the critically ill patients. This associated with the increased fluid intake and inadequate elimination. The management of fluid overload is by fluid removal with diuretic. Furosemide is a loop diuretic that frequently used as the initial therapy. However, the utilization of furosemide in the critically ill reminds a polarizing subject. The purpose of this study is to investigate the impact of furosemide on patients who are critically ill. Methods: The inclusion criteria included randomized controlled trials as well as observational cohort studies. The data sources utilized in this study were PubMed, Science Direct, ProQuest, and Cochrane.Results: We included 13 articles, of which 9 articles about generally critically ill patients with or without acute kidney injury (AKI), 2 articles about heart failure, and 2 articles about post operative. The furosemide was effective in generally critically ill patients with or without AKI, it can decrease the fluid balance, weight change, and improves the urine output. Furosemide had no harmful effect on kidney function. However, patients without oliguria were not recommended to receive high dose of furosemide. Critically ill patients with heart failure who received continuous infusion of furosemide were more susceptible to increased diuresis and greater depression of thoracic fluid content (TFC). Furthermore, it might cause the decrease of renal function. When compared to furosemide, continuous veno-venous hemodiafiltration (CVVHDF) was more successful at removing excess fluid, reducing weight, relieving symptoms, and improving hemodynamic and cardiac performance. In post operative patients, furosemide might cause metabolic alkalosis. Urinary electrolyte excretion rates were promptly altered by the use of low dose furosemide.Conclusion: Based on the patient's clinical data, furosemide use should be taken into consideration. In general, furosemide is effective to improve diuresis. Furosemide in the AKI condition with oliguria has beneficial effect. However, in heart failure condition, furosemide might affect renal function. In post operative, it might cause metabolic alkalosis. Further randomized controlled trial (RCT) is required.